EVALUASI KEBIJAKAN PEMBANGUNAN RUMAH LAYAK HUNI BAGI MASYARAKAT MISKIN DI KOTA SAMARINDA PROVINSI KALIMANTAN TIMUR - Ibnu Abbas (Jurnal Paradigma (JP), 2017)
The purpose of this study was to discover  how successful the development policies to built livable homes for the ooor by the Provincial Government of East Kalimantan in Samarinda, in terms of effectiveness, efficiency, adequacy, responsiveness, and accuracy so that later the results of this evaluation can provide an assessment and recommendation / suggestions for program improvement activities in the future. Sources of data taken from the informant and key informants and supported by secondary data analysis, were developed by Milles, Huberman.